Understanding recovery from object substitution masking - Goodhew, S.; Dux, P.; Lipp, Ottmar; Visser, T. (2012)
When we look at a scene, we are conscious of only a small fraction of the available visual information at any given point in time. This raises profound questions regarding how information is selected, when awareness occurs, and the nature of the mechanisms underlying these processes. One tool that may be used to probe these issues is object-substitution masking (OSM). In OSM, a sparse, temporally-trailing four dot mask can interfere with target perception, even though the target and mask have different contours and do not spatially overlap (Enns & Di Lollo, 1997). Here, we investigate the mechanisms underlying the recently discovered recovery from OSM observed with prolonged mask exposure (Goodhew, Visser, Lipp, & Dux, 2011). In three experiments, we demonstrate that recovery is unaffected by mask offset, and that prolonged physical exposure of the mask is not necessary for recovery. These findings confirm that recovery is not due to: (a) an offset transient impairing the visibility of other stimuli that are nearby in space and time, or (b) mask adaptation or temporal object-individuation cues resulting from prolonged mask exposure. Instead, our results confirm recovery as a high-level visual-cognitive phenomenon, which is inherently tied to target-processing time. This reveals the prolonged iterative temporal dynamics of conscious object perception. © 2011 Elsevier B.V.